The Effect of Toxic Workplace and Abuse of Power on Employee Performance at the Ministry X - Wulandari, Annisa Nur; Yulivan, Ivan; Jubaedah (Ilomata International Journal of Management, 2024)
This research was motivated by an increase in cases of employee complaints at the Ministry X regarding conflicts that occurred with leaders in work units. This research aims to determine and analyze the effect of toxic workplaces and abuse of power on employee performance through employee motivation. The method used in this research is a quantitative method where the data collection technique is by distributing questionnaires to 231 respondents with details of 220 civil servants and 11 government’s contractual employee within the Ministry X. Data analysis and processing techniques using the Partial Least Square (PLS) method. The results showed that (1) Toxic Workplace affects Employee Performance; (2) Abuse of Power has no effect on Employee Performance; (3) Toxic Workplace has no effect on Employee Performance with the mediation of Work Motivation; (4) Abuse of Power affects Employee Performance with the mediation of Work Motivation.